INVENTORY INTERNAL CONTROL ANALYSIS MEDICINE IN KARTIKA PULO MAS HOSPITAL - Asep Khusairi; Tri Handayani; Sunarti; Tito Prabowo (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2022)
Optimal drug inventory management can provide cost savings for drug procurement. Two problems are very important in controlling drug inventory, namely deciding the type and quantity of drugs to be ordered. To get a solution for controlling drug inventory, it is necessary to identify and analyze these problems. The purpose of this study is to analyze the control system and improve the efficiency of the patient's drug inventory management cycle at the Hospital Pharmacy Installation. Kartika Pulo Mas. This study analyzes the implementation of internal control of drug inventory in hospitals. Kartika Pulo Mas. in increasing the effectiveness and efficiency of internal control of drug sales in hospitals. Kartika Pulo Mas. The research method is a scientific way (rational, empirical and systematic) to obtain data with a specific purpose and use, the method that researchers use is the Qualitative Method. From the results of research and discussion that the authors have done at the RS. Kartika Pulo Mas, the authors conclude that the internal control of drug supplies at the hospital. Kartika Pulo Mas has been implemented properly and is running in accordance with applicable regulations. This can be seen from the stages of the SOP that have been implemented which include planning, implementation, reporting and follow-up has been carried out in accordance with applicable regulations.